Identification of amelogenin gene on burnt teeth samples through nested polymerase chain reaction amplification for sex identification - Lim, Jonathan Jun-Yong; Mohd Fadhli Khamis,; Nur Haslindawaty Abd Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Sex determination is one of the basic components in victim identification. This study aims to ascertain the sex of an individual from burnt teeth samples exposed at different temperature and time through nested polymerase chain reaction (PCR) on the amelogenin (AMEL) sex marker, to calculate the specificity and sensitivity, and to compare with previous relevant studies. A total of 17 teeth samples was subjected to burning at different temperatures ranging from 100°C to 500°C, at 2 to 10 minutes. The whole tooth was used for deoxyribonucleic acid (DNA) extraction by phenol-chloroform method. All samples were quantified for DNA concentration and then analyzed with nested PCR using two pairs of AMEL primer and results of sex typing were recorded. Out of 17 samples, genomic DNA extracted from 6 samples have concentrations ranging from 27.3 – 130.6 ng/μL. Nested PCR could amplify 16 samples for AMEL gene. Sex typing using AMEL gene showed 76.47% accuracy. Sensitivity of AMEL primer was increased from 6.67% to 63.64% using nested PCR technique; specificity of both external and internal primer was reported at 100%. Nested PCR of AMEL gene proved to be a suitable method for unequivocal determination of sex from degraded DNA samples.